Dietary selenium increases vitamin E contents of egg yolk and chicken meat - Skrivan, M; Marounek, M; Dlouhá, G; Sevcíková, S (British poultry science, 2008)
1. The influence of different forms of dietary selenium (Se) on vitamin E (alpha-tocopherol) and Se contents of egg yolk and chicken meat was investigated. 2. Eggs were collected from laying hens subjected to 4 different dietary treatments after 24 weeks of age. Treatments compared the effects of inorganic Se supplementation (selenite) to those of organic (Se-enriched yeast, Se-enriched alga Chlorella) supplements. In a second experiment the effect of the above organic dietary Se supplementation on the alpha-tocopherol contents of meat from broiler chickens was evaluated. 3. Dietary Se supplementation increased the alpha-tocopherol content of egg yolks from 297 mg/kg dry matter in treatment without supplementation to 311 mg/kg when selenium was supplemented as selenite, and to 370-375 mg/kg when organic supplements were used. The Se and alpha-tocopherol contents of breast and thigh meat in broilers were significantly increased by organic dietary Se supplementation. 4. The inclusion of organic dietary Se sources in the diets of laying hens and broilers would enhance the nutritional value (vitamin E and Se contents) of products (eggs and meat) for human consumption.
Keywords: Liver; játra; dieta; krmivo pro zvířata; alpha-Tocopherol; potravní doplňky; maso; mužské pohlaví; Nutritive Value; kur domácí; Egg Yolk; selen; nutriční hodnota; ženské pohlaví; Chickens; zvířata; Dietary Supplements; Meat; Selenium; Animal Feed; Diet; alfa-tokoferol; Female; vaječný žloutek; Male; Animals